Acoustical characterization of three Ottoman masjids built in Algeria. Issue 4 (December 2022) - Benferhat, Mohamed Ladaoui; Debache Benzagouta, Samira; Bouttout, Abdelouahab; Martellotta, Francesco
This paper aims at evaluating the acoustical quality of historical Ottoman masjids in Algeria. Measurements were carried out according to current international standards, allowing calculation of acoustical parameters including reverberation time, speech transmission index and Clarity. Three Ottoman masjids located in Algiers (Jedid, Ali-Bitchin, and Safir) were selected. The main purpose of the study was to evaluate the acoustics of the prayer hall in relation to its worship use, assuming as a reference studies of existing masjids. Results showed that two of three worship spaces are generally reverberant under unoccupied conditions (with mid frequency reverberation times of about 3 s), while the other has reverberation time of about 1 s at medium frequencies. Speech intelligibility under unoccupied conditions is between poor and fair for Jedid and Ali-Bitchin masjids, while in Safir masjid values were generally above 0.6. Presence of architectural elements made C50 values quite scattered and characterized by a clear non-symmetrical distribution. Calculations to consider the effect of occupancy were also performed, resulting in significantly drier acoustics with improved clarity.